Gender and sexuality in contemporary Greek theatre: red-light landscapes and city legends - Rosi, Lina (The Historical Review/La Revue Historique, 2020)
The article explores the representation of female sexuality, in particular prostitution and its association with urban landscapes. The subject forms part of a wider research venture examining the different ways in which contemporary Greek theatre depicts and discusses the female body, female discourse and women’s experiences. The analysis of recent productions focuses on two major points: first, on the mise en scène of the prostitute body and, second, on the way in which each production exposes the association between the characters’ biography and the geography and history of the city. Our aim does not lie in discussing the productions’ ideological views on the issue of prostitution and the contemporary sex industry, but in exploring the mode in which the stage narrative operates as a field in which the life story of these women is first heard and performed and then incorporated into the collective narrative of the city’s history. The productions discussed are Η τελευταία μάσκα–Fallimento (The Last Mask–Fallimento), based on a text by Kostas Logaras, adapted for the stage and directed by Thodoros Terzopoulos (2006); Η γυναίκα της Πάτρας (The Woman of Patras), based on a text by Giorgos Chronas and adapted for the stage and directed by Lena Kitsopoulou (2010); and Γκάμπυ (Gaby), based on Gabriella Ousakova’s autobiography, adapted for the stage by Anastasia Tzellou and Kirki Karali and directed by Karali (2015).